Тихий Дон: [роман] (Михаил Шолохов) - Шолохов Михаил Александрович (Азбука-классика, 2018)
Экземпляры: аб. ЦБ (20190218) / Инвентарный номер: 6180 / Цена: / Сис.шифр: Р2 / Авт.знак: Ш 78 / ГРНТИ: 17.82 / ББК: 84(2Pос=Рус)6